Programmno-celevoj princip upravlenija razvitiem personala v municipal'noj sisteme fiziceskoj kul'tury i sporta - Pasjukov, P. N.; Lopatin, A. P. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The program of professional training and improvement of professional skill of the personnel in the field of physical culture and sports described in the article represents the specific educational system developed according to the results of monitoring of the condition of physical culture and sports and the current health state of population, fea-tures of social and economic development of municipal education, demographic, cultural-national, nature-climatic and other factors. The application of the program-purpose principle in the practice of municipal management of the personnel devel-opment is the precondition of the steady development of the municipal system physical culture and sports in the modern living conditions of local communities.